Managing Symptom Profile of IBS-D Patients With Tritordeum-Based Foods: Results From a Pilot Study - Russo, Francesco; Riezzo, Giuseppe; Linsalata, Michele; Orlando, Antonella; Tutino, Valeria; Prospero, Laura; D'Attoma, Benedetta; Giannelli, Gianluigi (Frontiers in Nutrition, 2022)
In the past few years, increasing attention has been given to the pathologic role of specific foods in IBS, like wheat and other cereals. Recent literature describes IBS patients who may experience gastrointestinal (GI) and extra-GI symptoms precipitated by the ingestion of cereals. Tritordeum is a cereal of Spanish origin derived from the hybridization of durum wheat and wild barley. It is different from classic wheat for its gluten protein composition, with fewer carbohydrates and fructans and a higher content of proteins, dietary fibers, and antioxidants. This pilot study aimed to investigate the effects of a 12-week diet with Tritordeum-based foods in substitution of other cereals on the profile of GI symptoms (evaluated by appropriate questionnaire) and the health of the GI barrier (assessed by sugar absorption test and different markers of integrity and functions) in 16 diarrhea-predominant IBS (IBS-D) patients. The diet with Tritordeum-based foods (bread, bakery products, and pasta) significantly reduced IBS-D patients' symptoms. This amelioration appears to occur through an overall improvement of the GI barrier, as demonstrated by the reduced intestinal permeability and the decreased levels of markers of intestinal mucosal integrity, mucosal inflammation, and fermentative dysbiosis.